Data from: PROTAX-fungi: a web-based tool for probabilistic taxonomic placement of fungal ITS sequences ... - Abarenkov, Kessy; Somervuo, Panu; Nilsson, R. Henrik; Kirk, Paul M.; Huotari, Tea; Abrego, Nerea; Ovaskainen, Otso (Dryad, 2019)
• Incompleteness of reference sequence databases and unresolved taxonomic relationships complicates taxonomic placement of fungal sequences. We developed PROTAX-fungi, a general tool for taxonomic placement of fungal ITS sequences, and implemented it into the PlutoF platform of the UNITE database for molecular identification of fungi. • PROTAX-fungi outperformed the SINTAX and RDB classifiers in terms of increased accuracy and decreased calibration error when applied to data on mock communities representing species groups with poor sequence database coverage. • With empirical data on root- and wood-associated fungi, PROTAX-fungi identified reliably (with at least 90% identification probability) the majority of sequences to the order level but only ca. one fifth of them to the species level, reflecting the current limited coverage of the databases. • When applied to examine the internal consistencies of the Index Fungorum and UNITE databases, PROTAX-fungi revealed inconsistencies in the taxonomy database as ... : Root-associated fungi from GreenlandFungal ITS2 sequence data of root-associated fungi from Greenland in fasta format. DNA extracted from different plant species roots collected along the altitudinal gradient of Aucella mountain in the Zackenberg valley.root-associated fungi from Greenland.fas ...